Identifying Language Learning Strategies of Secondary School Students in Learning English as a Foreign Language - Sigit Aprisama (English Language Education Department, Universitas Majalengka, 2024)
Knowing students’ language learning strategies is very important in teaching a foreign language. The purpose of this study is to identify language learning strategies used by secondary school students in learning English as a foreign language. The participants of this study were 31 secondary school students in Singkawang. The questionnaires developed by Gursoy (2013) were used as the instrument of data collection in this study. The questionnaires consist of four factors in learning a foreign language, i.e., cognitive and metacognitive strategies and two social-languages, strategies to improve language learning, strategies of facilitation of the reception and production of the target language, and strategies for the consolidation of the target language. Overall, the result of the study shows that the students have strong strategies to study English as a foreign language. By knowing students’ strategies in learning a language is very important to teachers because it can give much information to the teachers for planning their teaching. Keyword: language learning strategies, foreign language, secondary school, students